A second-order maximum principle for singular optimal controls with recursive utilities of stochastic delay systems. (November 2019) - Hao, Tao; Meng, Qingxin
Abstract: This paper is devoted to the investigation of the second-order necessary conditions of singular control problems for controlled forward-backward delay systems in the case where the control domain is non-convex and the diffusion coefficients are independent of control. A second-order matrix-valued adjoint system is constructed to solve the obstacle caused by the product of the solution and its delay counterpart of the first-order variational equations. With the help of this observation, the second-order expansion of cost functional Y ε and the stochastic maximum principle are proved. Our work generalizes the classical case to the delay case